2010
DOI: 10.1007/s00414-010-0446-4
|View full text |Cite
|
Sign up to set email alerts
|

A new atlas for the evaluation of facial features: advantages, limits, and applicability

Abstract: Methods for the verification of the identity of offenders in cases involving video-surveillance images in criminal investigation events are currently under scrutiny by several forensic experts around the globe. The anthroposcopic, or morphological, approach based on facial features is the most frequently used by international forensic experts. However, a specific set of applicable features has not yet been agreed on by the experts. Furthermore, population frequencies of such features have not been recorded, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 15 publications
2
29
1
1
Order By: Relevance
“…The intraobserver mismatch percentages based on all features when using the DMV atlas ranged from 19% to 30%, whereas the interobserver error was approximately 39% (Ritz-Timme et al 2011). These results confirm that morphological classifications, although detailed and ameliorated with new facial features, are affected by an unavoidable subjectivity.…”
Section: Identification Of the Livingsupporting
confidence: 71%
“…The intraobserver mismatch percentages based on all features when using the DMV atlas ranged from 19% to 30%, whereas the interobserver error was approximately 39% (Ritz-Timme et al 2011). These results confirm that morphological classifications, although detailed and ameliorated with new facial features, are affected by an unavoidable subjectivity.…”
Section: Identification Of the Livingsupporting
confidence: 71%
“…When using the Anthropological Atlases for the categorization of facial features, this study showed that the inter-observer agreement in evaluating the features was poor; the mean mismatch percentage among observers being 46%. In comparison, Ritz-Timme et al [32] reported that when using one of the Atlases used in the present study, "The Anthropological Atlas of Male Facial Features" the mean inter-observer mismatch percentage was approximately 39%, while the intraobserver mismatch percentages ranged from 19% to 30%. In general, none of the classification patterns for the complete set of features on a single image and for age-different images of one person was the same for all three observers.…”
Section: Discussioncontrasting
confidence: 52%
“…Forensic anthropologists are often requested to compare the culprit represented on images with one or more suspects or compare individuals on different images. Three general approaches to facial identification are currently applied: morphological classification of facial traits (Ohlrogge et al, 2008(Ohlrogge et al, , 2009Ritz-Timme et al, 2011a;Vanezis et al, 1996), metric analysis (Halberstein, 2001;Kleinberg et al, 2007;Roelofse et al, 2008), and the superimposition method (De Angelis et al, 2009;Ventura et al, 2004;Yoshino et al, 2000Yoshino et al, , 2002Yoshino et al, , 2005. These approaches should help in standardising the comparison between two facial profiles, and the morphometric characteristics of the faces are described and compared in order to deliver a scientifically justifiable analysis.…”
Section: Introductionmentioning
confidence: 98%